Pengaruh Penggunaan Media Pembelajaran Powerpoint Terhadap Hasil Belajar pada Mata Pelajaran Informatika Kelas X SMAN 2 Padangsidimpuan - Parinduri, Rezti Deawinda; Supriadi, Supriadi; Zakir, Supratman; Okra, Riri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
With the development of digital technology in Indonesia realizing the needs of students, various alternative media exist to reach students without violating the system as a means of meeting students' needs in learning more efficientlyand effectively. One of the media that can be used for learning is PowerPoint media. Microsoft PowerPoint is widely used because of its easy operation, and everyone can make PowerPoint. The purpose of this study was to determinethe effect of using PowerPoint learning media on learning outcomes in Informatics class X SMA N 2Padangsidimpuan which is valid, practical, and effective. This type of research used by the author is quantitative research with experimental methods. The research design used was the Posttest-only Control Group Design. The sample of this research was students of class X semester 1 of class X Mia 1 and X Mia 2 SMA Negeri 2 Padangsidimpuan. The data collection technique is by using a test in the form of a Posttest. The data analysis technique used is an analysis prerequisite test consisting of a normality test and homogeneity test as well as hypothesis testing. Based on the results of this study, it was found that there were significant differences in studentlearning outcomes between the use of PowerPoint learning media and conventional learning methods in Informatics subjects, this can be seen from the posttest results of both classes. The results of the two tests illustrate the differencein the average student learning outcomes between the use of PowerPoint learning media and conventional learning methods in Informatics subjects, this can be seen from the posttest results of both classes. The results of the two testsillustrate the difference in the average student learning outcomes in the experimental class and the control class. By using PowerPoint learning media, students in the experimental class obtained a higher average score compared tothe scores of students who did not use PowerPoint learning media in the control class.